A systematic survey on reporting and methods for handling missing participant data for continuous outcomes in randomized controlled trials - Zhang, Yuqing (2017)
Objective: To assess analytic approaches randomized controlled trial (RCT) authors use to address missing participant data (MPD) for patient-important continuous outcomes. Study Design and Setting: We conducted a systematic survey of RCTs published in 2014 in the core clinical journals that reported at least one patient-important outcome analyzed as a continuous variable. Results: Among 200 studies, 187 (93.5%) trials explicitly reported whether MPD occurred. In the 163 (81.5%) trials that reported the occurrence of MPD, the median and interquartile ranges of the percentage of participants with MPD were 11.4% (2.5%-22.6%).Among the 147 trials in which authors made clear their analytical approach to MPD, the approaches chosen included available data only (109, 67%); mixed-effect models (10, 6.1%); multiple imputation (9, 4.5%); and last observation carried forward (9, 4.5). Of the 163 studies reporting MPD, 16 (9.8%) conducted sensitivity analyses examining the impact of the MPD and (18, 11.1%) discussed the risk of bias associated with MPD. Conclusion: RCTs reporting continuous outcomes typically have over 10% of participant data missing. Most RCTs failed to use optimal analytic methods, and very few conducted sensitivity analyses addressing the possible impact of MPD or commented on how MPD might influence risk of bias. (C) 2017 Elsevier Inc. All rights reserved.